ADAPTATION STRATEGIES OF FOOD SECURITY FOR CLIMATE CHANGE - Shrestha, Sajani (International Journal of Environment, 2015)
The Rupa lake area in Lekhnath Municipality of Kaski district, at Rupa Lake basin areas of Nepal was selected to explore the impacts of climate change on livelihoods in term of food security. 20% of the wetland dependent communities constituted of sample household (HHs). Semi-structured questionnaire was taken for focused group consultations. It was found that majority of population (87%) of lake basin is dependent on agriculture for food security. There is a year-round food security for 50% of sample HHs, with 22% of this having surplus food. About 5% of HHs has food security for less than three months where as 19% HHs have food security for more than six months. Within this scenario, over 90% HHs responded to climate change in the form of rise in temperature (74%); unpredictable rainfall (77%); shift in rainfall (64%); and phonological changes (51%). About 74% of households are aware about the effect of climate change and had adopted different strategies to resist against the effect of climate change. Out of the 74% of HHs, more than 50% of the household use chemical fertilizers and agricultural inputs and other means to cope small shop (business), service, labor and remittance against the climate change. International Journal of Environment Volume-4, Issue-3, June-August 2015 Page: 11-19